Enhancing parliamentary oversight for effettive security sector reform in democratic Nigeria (2015)
The provision of the most essential public good - security in accordance with the will of the people is very germane to the consolidation of democratic governance. Though, the Nigerian state is set to inaugurate her 8th National Assembly on 9th June, 2015, the capacity of the nation’s parliamentary body (National Assembly) to provide effective parliamentary oversight over the nation’s security sector for the establishment of a democratic security forces is grossly deficient. In light of this, the objective of this paper is to explore how the Nigeria’s parliamentary body can be energized in the performance of its oversight functions over the nation’s security sector. The study employed the descriptive survey research method. It was revealed that the inadequate capacity of the parliamentarians in the performance of their oversight functions partly accounts for the incessant violation of the fundamental human rights of the people by the nation’s security forces. Thus, it becomes imperative that the capacity of the nation’s parliamentary body to carry out her oversight responsibilities be greatly strengthened. This, the paper posits can be achieved when there is a considerable improvement in the knowledge base of the parliamentarians on the workings of the entire security sector and the logic and methods of her performance of the oversight functions and a comprehensive review of the constitution with a view to freeing the security forces from the exclusive control of the presidency. The paper concludes that it is only when there is an effective parliamentary oversight over Nigeria’s security agencies that the prevalent executive control over the sector can be moderated in line with democratic principles and practices.